Communication Patterns of Teachers of Moral Creeds on the Moral Development of Class IX Students of Mts Aisyiyah Medan - Ramadhani, Rohdearna; Nasution, Mawaddah (Cattleya Darmaya Fortuna, 2022)
Morals in Islam become something important and must be considered. Islam is a religion that teaches about adab or morals in humans and that is the most important thing before studying. Morals are one of the main teachings in Islam. Good morals will weigh the scales of a person's goodness on the Day of Resurrection. This research was carried out to: (1) determine the application of the communication pattern of the moral aqeedah teacher in fostering the morals of students at Mts Aisyiyah Medan (2) the supporting and inhibiting factors of the communication pattern of the teacher of moral creed in the moral development of students at Mts Aisyiyah Medan. This research is a qualitative research. This research is a field research and this research is classified as a qualitative descriptive research. Data were collected by conducting observations, documentation and interviews. The process of the communication pattern of the moral aqeedah teacher towards the moral development of class IX students at Mts Aisyiyah Medan is to combine the three communication patterns that are often done, but at certain times the moral aqidah teacher only uses one communication pattern. such as one-way communication patterns, interpersonal communication patterns or two-way communication, and group communication or multi-way communication.